2016
DOI: 10.1113/jp272703
|View full text |Cite
|
Sign up to set email alerts
|

Formation of mitochondrial‐derived vesicles is an active and physiologically relevant mitochondrial quality control process in the cardiac system

Abstract: The formation of mitochondrial-derived vesicles (MDVs), a process inherited from bacteria, has emerged as a potentially important mitochondrial quality control (QC) mechanism to selectively deliver damaged material to lysosomes for degradation. However, the existence of this mechanism in various cell types, and its physiological relevance, remains unknown. Our aim was to investigate the dynamics of MDV formation in the cardiac system in vitro and in vivo. Immunofluorescence in cell culture, quantitative transm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
157
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(162 citation statements)
references
References 44 publications
4
157
0
1
Order By: Relevance
“…Theses vesicles are independent of Drp1 and have a diameter between 70 to 150nm [15, 16]. MDVs are produced in baseline conditions in cardiac H9C2 cells and in mouse heart tissue [17]. Stress increases the formation of these MDVs as observed after treatment with doxorubicin or antimycin A, in association with cardiac dysfunction [17, 18].…”
Section: Mitochondrial Quality Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Theses vesicles are independent of Drp1 and have a diameter between 70 to 150nm [15, 16]. MDVs are produced in baseline conditions in cardiac H9C2 cells and in mouse heart tissue [17]. Stress increases the formation of these MDVs as observed after treatment with doxorubicin or antimycin A, in association with cardiac dysfunction [17, 18].…”
Section: Mitochondrial Quality Controlmentioning
confidence: 99%
“…MDVs are produced in baseline conditions in cardiac H9C2 cells and in mouse heart tissue [17]. Stress increases the formation of these MDVs as observed after treatment with doxorubicin or antimycin A, in association with cardiac dysfunction [17, 18]. The formation of MDVs appears to be prior to mitophagy [15], suggesting a role for MDVs as a first defense before mitophagy, which is costlier for the cell.…”
Section: Mitochondrial Quality Controlmentioning
confidence: 99%
“…Subsequently, this frees up constriction sites for the recruitment and/or activation of Drp1 and promotes mitochondrial fission and fragmentation . MDVs are defined as structures with diameters of 70 to 150 nm, and are considered quality control mechanisms for mitochondria that deliver mitochondria‐related contents to the late endosome or multivesicular bodies . Although the exact mechanism of incorporation of the selected cargo is unclear, studies have shown that both the outer and inner membranes can be used to form MDVs, carrying membrane bound or mitochondrial matrix proteins .…”
Section: Expanding the Regulation Of Mitochondrial Fusion And Fissionmentioning
confidence: 99%
“…New tools for experimental manipulation of autophagy in cardiac disease states are under development, which can potentially allow tissue selective autophagy interventions targeted specifically to macro-autophagy processes. This is important in order to distinguish macro-autophagic processes from other related autophagic pathways also operational in most cell types, namely micro-autophagy (direct recruitment of cytosolic material to the lysosome 4 ), chaperone-mediated autophagy/endosomal micro-autophagy (single protein-recruitment to endosomes/lysosomes 5, 6 ) and mitochondria-derived vesicular autophagy (fusion of mitochondrial outer membranes with endosomes prior to lysosome degradation 7 ). This review focus is on macro-autophagy pathways and processes – and in particular highlights recent advances in defining the role of cargo-selective macro-autophagy subtypes in myocardial stress settings.…”
Section: Introductionmentioning
confidence: 99%